Polyethyleneimine-grafted polyphosphazene microspheres for rapid and efficient capture of anionic dyes from wastewater. (August 2021) - Yu, S.; Feng, M.; Wu, P.; Liu, H.; Liu, S.; Fu, J.
Abstract: Developing novel adsorbent to capture organic contaminants from wastewater rapidly and efficiently is highly desirable for waste treatment and environmental restoration. Herein, we reported a new amino-rich spherical adsorbent (PZS-PEI) for highly-efficient uptake of anionic dyes from aqueous solution. The PZS-PEI adsorbent was fabricated through a two-step process including synthesis of PZS-Cl microspheres via room temperature polymerization of hexachlorocyclotriphosphazene with bis(4-hydroxyphenyl) sulfone and subsequent surface grafting reaction of PZS-Cl microspheres using branched polyethyleneimine (PEI). The microstructure of as-obtained PZS-PEI microspheres was fully characterized by scanning electron microscopy, Fourier transform infrared, X-ray photoelectron spectroscopy, zeta potential, and N2 adsorption test. The adsorption performance of the PZS-PEI microspheres towards organic dyes was evaluated through carrying out a series of studies including various influence factor analysis, adsorption isotherm, kinetics, and thermodynamics. Results show that the PZS-PEI adsorbent owned good adsorption selectivity towards anionic dyes, and the maximum adsorption capacities for methyl orange (MO), acid chrome blue K, eosin-Y reached 190.29, 152.90, and 92.34 mg/g at 25 °C, respectively. In addition, the uptake behavior of organic dye by the PZS-PEI adsorbent conformed to Freundlich isotherm and pseudo-second order kinetic model, and the adsorption process followed a three-stage intraparticle diffusion mode with an endothermic and spontaneous characteristic. Electrostatic interaction and hydrogen bonding were responsible for the highly-efficient adsorption of the PZS-PEI adsorbent towards typical anionic dye MO. Graphical abstract: An amino-rich spherical adsorbent (PZS-PEI) was facilely synthesized through a two-step strategy, which could display high-efficient adsorption ability toward anionic dyes. Image 1 Highlights: A novel amino-rich spherical adsorbent was fabricated at room temperature. The adsorbent exhibited rapid and efficient capture ability towards anionic dye. The adsorbent owned superior adsorption selectivity towards anionic dye. This spherical adsorbent displayed good reusability.